In the Arctic seas. A narrative of the discovery of the fate of Sir John Franklin and his companions. - M'Clintock, Francis Leopold, Sir, 1819-1907. (Philadelphia, Porter & Coates, 1859)
Author's ed. Mode of access: Internet.